Analysis of Tools Used in Assessing Technical Skills and Operative Competence in Trauma and Orthopaedic Surgical Training: A Systematic Review - James, Hannah K. (JBJS Rev, 2020)
Robust assessment of skills acquisition and surgical performance during training is vital to ensuring operative competence among orthopaedic surgeons. A move to competency-based surgical training requires the use of tools that can assess surgical skills objectively and systematically. The aim of this systematic review was to describe the evidence for the utility of assessment tools used in evaluating operative performance in trauma and orthopaedic surgical training. METHODS: We performed a comprehensive literature search of MEDLINE, Embase, and Google Scholar databases to June 2019. From eligible studies we abstracted data on study aim, assessment format (live theater or simulated setting), skills assessed, and tools or metrics used to assess surgical performance. The strengths, limitations, and psychometric properties of the assessment tools are reported on the basis of previously defined utility criteria. RESULTS: One hundred and five studies published between 1990 and 2019 were included. Forty-two studies involved open orthopaedic surgical procedures, and 63 involved arthroscopy. The majority (85%) were used in the simulated environment. There was wide variation in the type of assessment tools in used, the strengths and weaknesses of which are assessor and setting-dependent. CONCLUSIONS: Current technical skills-assessment tools in trauma and orthopaedic surgery are largely procedure-specific and limited to research use in the simulated environment. An objective technical skills-assessment tool that is suitable for use in the live operative theater requires development and validation, to ensure proper competency-based assessment of surgical performance and readiness for unsupervised clinical practice. CLINICAL RELEVANCE: Trainers and trainees can gain further insight into the technical skills assessment tools that they use in practice through the utility evidence provided.